Peralihan Fokalisasi serta Ambiguitas Narator dan Tokoh sebagai Strategi Defokalisasi pada Narasi Novel Seperti Dendam, Rindu Harus Dibayar Tuntas Karya Eka Kurniawan - Komariya, Siti; Prades Pratiwi, Dyani; Nurul Qarimah , Aryana (Universitas Andalas, 2025)
Magical realism is a branch of science that is still relevant to be discussed today. Defocalization, which is a strategy of magical realism, is one of the ways to define a magical realism narrative by using a distinctive strategy in its storytelling style. Two forms found in the defocalization strategy are focalization switching and narrator ambiguity. The purpose of this study is to reveal the shift of focalization which then affects the ambiguity of the narrator. The theory used is magical realism by Wendy B. Faris by highlighting the Defocalization section. The novel Seperti Dendam, Rindu Harus Dibayar Tuntas has two forms of defocalization strategies and narrator ambiguity as part of the defocalization strategy offered in the form of ambiguous dialogue narration. From the switch of focalization, the ambiguity of the narrator emerges, which makes the narrative more confusing. This study found that in this novel several narratives contain focalization switches which then cause ambiguity in the position of the narrator. However, the novel also asserts that the switch of focalization and ambiguity of the narrator are not influenced by something magical because the role of the narrator and the character is more than the role of something else (magical).